Analysis and optimization of the sustainability of oilseed-based biofuels production systems in West Africa - (:unkn) unknown (My University, 2018)
The profitability of biofuel production chains is a prerequisite to their competitiveness with fossil fuels. Profitability depends on several intrinsic factors related to processing technology and the organization of these sectors.In this thesis, we will study in particular Jatropha Curcas, Balanites aegyptiaca and sunflower supply chains. The aims are to evaluate and optimize the sustainability conditions of biofuel production chain of in West Africa.Starting by potentially existing chains in West Africa, a model will be proposed to calculate the costs and environmental impacts of biofuel production systems taking into account the geographic data on the fields, seasonal constraints, geographical constraints and the availability of resources. This study will also include the analysis and optimization of technological options and biofuel production processes. Thus after defining the relevant criteria and indicators for sustainable development, it will be: provide an assessment model of these criteria for networks studied taking into account the option of valorization of co-products; design a multicriteria tool in order to evaluate the performance of biofuel production systems; develop a tool or "decision support system" for policy makers and those involved in the studied sectors; study not only the technical aspects of oilseed processing into biofuel, but also introduce into the calculations system, the cost which allows to produce seeds, carry them to the unit, and perform their transformation.
Keywords: African Research